Preclinical platforms to study therapeutic efficacy of human γδT‐cells for oncology indications. Issue 2 (12th June 2022) - Barisa, Marta; Fowler, Daniel; Nattress, Callum; Fisher, Jonathan
Abstract: In this commentary, we discuss recent advances in the study of γδT cell‐based immunotherapeutics. As an allo‐compatible cell therapy chassis without clear functional homologs in mice, γδT cells represent a challenge and an opportunity for preclinical modelling. We discuss some of the techniques and approaches that can be used to demonstrate and characterise γδT cell behaviour in biomimetic systems.